THE EFFECT OF ORGANIZATIONAL COMMUNICATION ON THE PERFORMANCE OF MUHAMMADIYAH YOUTH IN MEDAN CITY - Datuk Imam Marzuki; MARLINA MA (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This population research is the board of Muhammadiyah Youth of Medan , amount to 41 people . Sample of this research is conducted in a total sampling technique . The results showed that the influence of organizational communication variables influence on organizational performance variable at 2.2 %, while the influence of leadership style of chairman variable on organizational performance shows that the R square value of 0.131 means the leadership style of chairman variables influence on organizational performance variable at 13 , 1 %, the variable effect of organizational communication and leadership styles of the chairman on the organizational performance showed that the R value of 0.253 square variables . Thus the variable organizational communication and leadership style of chairman is jointly influence on organizational performance variable by 25.3 % while the remaining amount of 74.7 % determined by other variables note examined . These results it can be concluded that the influence of organizational communication and leadership style of chairman on the performance of the Youth Muhammadiyah is significant influence and can be the material for all readers in the development of science.